Manajemen Anestesi Perioperatif pada Pasien Obesitas: A Literature Review - Alya Nabila Nurrahma; Andre Kusuma Rakhman (Medula, 2026)
The prevalence of obesity has continued to rise over the past decades and has become a major concern in clinical practice. Obesity presents specific challenges in perioperative management, particularly in airway management for obese patients undergoing surgical procedures. Anesthesiologists must understand the various risks associated with anatomical and physiological changes, including excessive fat deposition in the neck and thoracic regions, reduced functional residual capacity of the lungs, and increased oxygen demand. In addition, obese patients frequently have comorbid conditions such as diabetes mellitus, hypertension, and obstructive sleep apnea, which further increase the risk of perioperative complications. This article was prepared using a literature review method through a comprehensive search of scientific articles published in various journals. The literature included publications from 2020 to 2025 obtained from PubMed, NCBI, and Google Scholar databases. Selected articles were analyzed using a systematic literature review approach, which involved data collection, assessment of study quality, and synthesis of findings with a focus on perioperative management in obese patients. The results indicate that successful anesthetic management in obese patients strongly depends on thorough preoperative assessment, careful airway strategy planning, and appropriate selection of anesthetic techniques. During the intraoperative phase, close monitoring and adjustment of anesthetic drug dosing are essential to maintain patient safety. Postoperative care also plays a crucial role in preventing respiratory complications, particularly in the early recovery period. A comprehensive and integrated perioperative approach is required to improve patient safety and optimize clinical outcomes in obese individuals undergoing surgery.